A reflectionless compact elliptical half Maxwell fish-eye lens designed by transformation optics - Eskandari, Hossein (Frontiers in Materials, 2022)
A two-dimensional half Maxwell fish-eye lens is compressed using a linear transformation that maps a half circle to a half ellipse. The focusing property of the lens is preserved while making the device more compact. The boundary reflections, investigated for both TE and TM polarizations, were suppressed for beams directed toward the optical axis of the lens. A designed prototype provided a scanning range of ±20° with negligible reflections. The design’s functionality was verified using COMSOL multiphysics.